2017
DOI: 10.1021/acs.langmuir.7b02330
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion Solvent Evaporation-Induced Self-Assembly of Block Copolymers Containing pH-Sensitive Block

Abstract: A simple yet efficient method is developed to manipulate the self-assembly of pH-sensitive block copolymers (BCPs) confined in emulsion droplets. Addition of acid induces significant variation in morphological transition (e.g., structure and surface composition changes) of the polystyrene-block-poly(4-vinylpyridine) (PS-b-P4VP) assemblies, due to the hydrophobic-hydrophilic transition of the pH-sensitive P4VP block via protonation. In the case of pH > pKa (pKa = 4.8), the BCPs can self-assemble into pupa-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 57 publications
(83 reference statements)
6
57
0
Order By: Relevance
“…Interfacial instability is a contemporary topic that is extensively studied in polymer science to develop novel morphologies, with one example being hierarchically structured microparticles during solvent removal from oil‐in‐water emulsions . The fundamental principle is that the interface is full of fluctuations and the undulation amplitude is controlled by the interfacial tension.…”
Section: Resultsmentioning
confidence: 99%
“…Interfacial instability is a contemporary topic that is extensively studied in polymer science to develop novel morphologies, with one example being hierarchically structured microparticles during solvent removal from oil‐in‐water emulsions . The fundamental principle is that the interface is full of fluctuations and the undulation amplitude is controlled by the interfacial tension.…”
Section: Resultsmentioning
confidence: 99%
“…Yellow (and their corresponding bars) represents our and commonly used stabilizers, while red (and their corresponding bars) is denoted as commonly reported materials in synthesizing biodegradable and/or nonspherical nanoparticles for drug delivery and targeting. Abbreviations and further details of referred material–nanoparticles: SDS (sodium dodecyl sulfate), (2) Docusate‐Na, (3) Triton X‐100, (4) Na‐Cholate & ‐Deoxycholate, (5) PVP (poly(vinylpyrrolidone)), (6) PEG (poly(ethylene glycol)) 6000, (7) Dextran, (8) Poloxamer 188, (9) HSA (human serum albumin), (10) Chitosan, (11) Cyanoacrylate, (12) PS‐COOH (carboxylated poly(styrene)), (13) PS (poly(styrene)), (14) PDMS (poy(dimethylsiloxane)), (15) PMMA (poly(methyl methacrylate)), (16) PHEA (poly(hydroxyethyl acrylate)), (17) PHEMA (poly(hydroxyethyl methacrylate)), (18) PEGDA (poly(ethylene glycol) diacrylate)‐PHEMA (poly(hydroxyethyl methacrylate)), (19) CEA (2‐carboxyethyl acrylate), (20) PBLG (poly(γ‐benzyl l ‐glutamate)), (21) Triglyceride (cocoa butter), (22) P4VP (poly(4‐vinyl pyridine)), (23) Au (gold), and (24) SWCNT (single‐walled carbon nanotubes) …”
Section: Resultsmentioning
confidence: 99%
“…First, beside well‐defined amorphous aliphatic polyesters and PS‐COOH studied here, another best example for the aforementioned hypothesis is poly(4‐vinyl pyridine) (P4VP), an amorphous and a weakly hydrophilic polymer (Figure e). Likewise the aliphatic polyesters, P4VP (grafted by PS) exhibits shape‐memory properties depending on media pH . In contrast to aliphatic polyesters, the P4VP hydrophobicity becomes lesser at pH lower than its p K a (5.5) and reaches maximum at higher pH .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the deepening of the research and the improvement of the experimental technique, the researchers find that the onion‐like vesicles with different layers can be obtained through the self‐assembly of the polymer systems . For example, Kang et al studied the self‐assembly of the comb‐like amphiphilic copolymers in aqueous media and observed that the number of wall layers is dependent on the concentration of polymers in the aqueous media .…”
Section: Introductionmentioning
confidence: 99%